2006
DOI: 10.1021/ie0600902
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Boron Doping on Photocatalytic Activity and Microstructure of Titanium Dioxide Nanoparticles

Abstract: Boron-doped TiO 2 nanoparticles were prepared by the sol-gel method and characterized by XRD, TEM, XPS, FT-IR, and UV-vis spectroscopy. XRD results showed that the doping of boron ions could efficiently inhibit the grain growth and facilitate the anatase-to-rutile transformation prior to the formation of diboron trioxide phase. FT-IR and XPS results revealed that the doped boron was present as the form of B 3+ in B-doped TiO 2 samples, forming a possible chemical environment like Ti-O-B. The lattice parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
291
1
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 452 publications
(334 citation statements)
references
References 62 publications
27
291
1
5
Order By: Relevance
“…This effect has been previously reported for similar catalysts and 19 it has been attributed to the restrained TiO 2 crystal growing due to the existence of 20 large amount of boron [16,17,18]. 21…”
mentioning
confidence: 52%
“…This effect has been previously reported for similar catalysts and 19 it has been attributed to the restrained TiO 2 crystal growing due to the existence of 20 large amount of boron [16,17,18]. 21…”
mentioning
confidence: 52%
“…This is due to the fact that the ion radius of B(III) (0.023 nm) is much smaller than that of Ti(IV) (0.064 nm). Therefore, boron oxides existing at the surface of the material can easily incorporate into the crystalline framework of titania [21,34]. Figure 3a shows XRD spectra registered for boron-doped and pure titania layer.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, doping of TiO 2 with boron has been widely studied in terms of its effect on the surface and the bulk structure which changes the ability of tailoring the bandgap, suppresses electron-hole pairs from recombination, and improves electron conductivity [21][22][23]. Some papers have reported that B-doped TiO 2 powders obtained by a modified sol-gel method showed a red-shifted absorption spectrum [24,25], while other studies concern increase in the bandgap energy of TiO 2 upon doping when H 3 BO 3 was used as a boron precursor because of the decrease of the crystal size after incorporation of boron atoms [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…目前, Pt, Ru, Pd, Au 和 Ag 等贵金 属改性的 TiO 2 已广泛应用于光催化还原 CO 2 研究 中 [18,19] . 研究表明, N [20] , I [21] , C [22] , S [23] 和 B [24] 等非金属 的掺杂可以降低 TiO 2 的禁带宽度, 提高 TiO 2 的可见光 催化活性.…”
unclassified